Expressing Political and Religious Identity: Religion-Science Relations in Indonesian Muslim Thinkers 1970-2014 - Bahri, Media Zainul (Al-Jamiah: Journal of Islamic Studies, 2018)
An attractive phenomenon of Indonesian Islam in 1990s era up to the recent time is an emergence of thought battle within Muslim scholars concerning religon and science. From the struggle, various terms have arisen such as: Islamization of knowledge/science, scientification of Islam, objectification of Islam, compatibility, ayatization or ayatisasi (from Arabic Äya [verse, sign] i.e. to find the QurâÄnic Äya for every single knowledge/science finding), integration, integration-interconnection, and so forth. According to the typology of Ian Barbour, instead of conflict and independence, religion-science relations in Indonesian Islam are always in the position of integration and dialogue. However, this article focuses on how the discourse of religion-science relations is conducted to express Islamic identity and political become more salient and stronger, particularly within Indonesian urban Muslims. Since the pioneers in 1970s to1980s such as Rasjidi, Moenawar Chalil, Buya Hamka and Syekh Kadirun Yahya, then more academic discourse such as the figures of Hidajat Nataatmaja, Kuntowijoyo, Mulyadhi Kartanegara and Amin Abdullah, to very popular writers of ayatisasi, Islamization of science has--at least three main agendas: the politics to strengthening Muslim identities, the spirit against secularist-Western, and apologetic attitudes as part of the theological campaign. This popular phenomenon shows that Islam is not merely regarded as âa perfect religionâ in terms of ethics, ritual as well as spiritual, but also it is kind of âIslamic revivalâ, i.e. a politically meaningful term, ârevival of the ummah in all its aspectsâ.[Salah satu fenomena menarik islam Indonesia tahun 1990an hingga sekarang adalah perdebatan pendapat diantara ilmuwan muslim terkait hubungan agama dan sains. Dari perdebatan tersebut setidaknya memunculkan istilah seperti islamisasi pengetahuan atau ilmu, ilmuisasi islam, obyektifikasi islam, keserasian, ayatisasi, integrasi, integrasi â interkoneksi, dan lainnya. Berdasarkan tipologi dari Ian Barbour, alih-alih konflik dan independensi, hubungan agama dan sains di muslim Indonesia lebih tepat berada diposisi integrasi dan dialog. Dalam artikel ini fokus tertuju pada bagaimana wacana hubungan agama dan sains sebagai ekspresi identitas politik dan keislaman, khususnya pada muslim perkotaan. Sejak 1970-1980an mulai dikenal nama-nama seperti Rasjidi, Moenawar Chalil, Buya Hamka dan Kadirun YahyaÂ  hingga nama â nama yang lebih akademis seperti Hidajat Nataatmaja, Kuntowijoyo, Mulyadhi Kartanegara dan Amin Abdullah. Setidaknya ada tiga agenda dari gerakan ini yaitu politik penguatan identitas keislaman, semangat melawan sekulerisasi barat dan sikap defensif yang merupakan bagian dari dakwah. Singkatnya, fenomena ini menunjukkan bahwa islam tidak hanya sebagai agama yang sempurna secara etis, tapi juga ini bagian dari kebangkitan islam seperti dalam istilah politiknya, kebangkitan islam di segala aspeknya.]Â